The Spanish Civil War, the Soviet Union, and communism - Payne, Stanley G. (New Haven : Yale University Press, 2004)
In this compelling text Stanley Payne offers a comprehensive narrative of Soviet and Communist intervention in the revolution and Civil War in Spain. He documents Soviet strategies Comintern activities and the role of the Communist party in Spain from the early 1930s to the end of the Civil War in 1939.
Soviet policy and the Comintern in the early years, 1917-1925 -- Communism and revolution in Spain, 1917-1931 -- Communism and the Second Republic, 1931-1934 -- From revolutionary insurrection to popular front, 1934-1936 -- Communism and the implosion of the republic, February-July 1936 -- Communism and the Spanish Revolution, July-August 1936 -- The Soviet decision to intervene militarily, July-October 1936 -- Soviet military participation, 1936-1939 -- The policy struggle under the Largo Caballero government, September 1936-May 1937 -- The Negr?in government, 1937-1938 -- Defeat, 1938-1939 -- Conclusion.
Includes bibliographical references (pages 319-377) and index.
Print version record.
JSTOR
Keywords: Communist International -- History; Internationale communiste -- Histoire; Communist International; Communism -- Soviet Union; Communism -- Spain; Soviet Union -- Relations -- Spain; Spain -- History -- 1868-1931.; Spain -- History -- Civil War, 1936-1939.; Spain -- History -- Republic, 1931-1939.; Spain -- Relations -- Soviet Union; Communisme -- Espagne; Communisme -- URSS; URSS -- Relations -- Espagne; Espagne -- Relations -- URSS; Espagne -- Histoire -- 1868-1931.; Espagne -- Histoire -- 1931-1939 (République); Espagne -- Histoire -- 1936-1939 (Guerre civile); HISTORY; HISTORY -- Europe -- Spain & Portugal; Communism; International relations; Soviet Union; Spain; Tweede Republiek (Spanje); Spaanse burgeroorlog; Communisme; Buitenlandse interventie; 1868 - 1939; Computer network resources; Computer network resources; History